Conditions and Directions of Humanities-Based Knowledge Transformation - Pramod Kumar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
In this research the factors, preconditions and directions for the transformation of knowledge based on humanities that enable education innovations to be introduced within research universities. The first section of paper explains the concepts of organizational and applying education research based on creativity. The guidelines depend upon an ethnomethodology evaluation, micro as well as interaction ethnology. The other section of paper concentrates over examples that are tailored for creative research university goals. Similar implementation enables the description of the members, the modes of their implementation and the criteria of their effectiveness to be measured. These activities face a challenge of selfmodification and of turning universities into environments that can form a modern concept & unequaled functional types involvement within normal environment in order to choose such study, it is believed that exposure to the functioning of micro-level educational processes is the key to the management of educational developments. Such procedures must be transparent and tactically and strategically compatible with the changes occurring at a university.